2009
DOI: 10.1016/j.yqres.2008.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cosmogenic nuclides document complex Pleistocene exposure history of glacial drifts in Terra Nova Bay (northern Victoria Land, Antarctica)

Abstract: Geomorphological and glacial geological surveys and multiple cosmogenic nuclide analyses ((10)Be, (26)Al, and (21)Ne) allowed Lis to reconstruct the chronology of variations prior to the last glacial maximum of the East Antarctic Ice Sheet (EAIS) and valley glaciers in the Terra Nova Bay region. Glacially scoured coastal piedmonts with round-topped mountains occur below the highest local erosional trimline. They represent relict landscape features eroded by extensive ice overriding the whole coastal area befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 36 publications
4
29
0
6
Order By: Relevance
“…This scenario is similar to the thermal state envisaged for late Miocene and Pliocene ice in northern Victoria Land (Smellie et al 2014), and by modelling studies of the modern Antarctic ice sheet in East Antarctica (Pollard and De Conto 2009;Pattyn 2010). Erratics showing similar edge abrasion and surface oxidation/weathering are common in the region and are known as Terra Nova Drift (Baroni and Orombelli 1987;Orombelli et al 1990;Di Nicola et al 2009). Similarly abraded erratics exposed at c. 16 ka are also present at Cape Adare at 350 m a.s.l., c. 400 km to the north .…”
Section: Environmental Implicationssupporting
confidence: 66%
See 2 more Smart Citations
“…This scenario is similar to the thermal state envisaged for late Miocene and Pliocene ice in northern Victoria Land (Smellie et al 2014), and by modelling studies of the modern Antarctic ice sheet in East Antarctica (Pollard and De Conto 2009;Pattyn 2010). Erratics showing similar edge abrasion and surface oxidation/weathering are common in the region and are known as Terra Nova Drift (Baroni and Orombelli 1987;Orombelli et al 1990;Di Nicola et al 2009). Similarly abraded erratics exposed at c. 16 ka are also present at Cape Adare at 350 m a.s.l., c. 400 km to the north .…”
Section: Environmental Implicationssupporting
confidence: 66%
“…The distribution of the abraded erratics described in this paper and by other authors (e.g. Baroni and Orombelli 1987;Orombelli et al 1990;Di Nicola et al 2009) may suggest that polythermal ice had a widespread distribution in the Mt. Melbourne hinterland during the last glacial, and potentially extended along 400 km of coastal Victoria Land (Harrow Peaks-Cape Adare), at least.…”
Section: Environmental Implicationssupporting
confidence: 64%
See 1 more Smart Citation
“…To determine whether a sample has a simple or a complex exposure history, the measurement of more than one nuclide is necessary (Anderson et al 1996;Briner et al 2006;Di Nicola et al 2009). The radioactive decay of 10 Be and 26 Al with time will result in a decrease in concentrations of these radionuclides in quartz.…”
Section: Cosmogenic Radionuclide Datingmentioning
confidence: 99%
“…By plotting such ratio changes in two-nuclide diagrams, one can determine whether a sample experienced a simple or a complex exposure history (i.e. periods of exposure broken by periods of total or partial isolation from cosmic rays) or was exposed to distinct thermal regimes at the bed of former glaciers Miller et al 2006;Di Nicola et al 2009). In these studies it has been shown that a cold-based glacier regime does not erode the bedrock surface sufficiently to eliminate radionuclide isotopes from the former ice-free period.…”
Section: Cosmogenic Radionuclide Datingmentioning
confidence: 99%